Experimental Investigation on Carbonation Behavior in Lime-Stabilized Expansive Soil - Long Xu; Fusheng Zha; Congmin Liu; Bo Kang; Jingjing Liu; Chuang Yu (Advances in Civil Engineering)
The carbonation behavior of lime-stabilized expansive soil is important for assessing the stabilization efficiency from the perspective of durability. In this study, the accelerated carbonation tests, measurement of pH value distribution, and the free swell ratio tests were conducted to investigate the evolutions of carbonation depth, carbonation extent, and expansive potential of lime-stabilized expansive soil. XRD, MIP, and SEM techniques were adopted as supplements to reveal the carbonation mechanism. Results demonstrated that the carbonation depth of lime-stabilized expansive soil increased significantly as time elapsed; however, the rate of increase reduced when the carbonation time increased. Higher carbonation depth was obtained at higher temperature and CO2 concentration and lower relative humidity, which was described by an empirical model. Fully, partly, and noncarbonated zones were subsequently presented with an increase in the depth of the soil. The expansive potential of lime-stabilized expansive soil was partially recovered during carbonation. The obtained linear relationships between the free swell ratio and pH value were adopted to describe the evolution of expansive behavior with carbonation time and depth. In microstructural analysis, the conversion of portlandite into calcium carbonate was significant, which resulted in changes in microstructure and controlled the carbonation behavior.